FENOMENA ANGKRINGAN PADA HUBUNGAN SOSIAL REMAJA DI KOTA MOJOKERTO - Yanuar Sinatra (Jurnal Neo Societal, 2023)
The purpose of this study was to determine the activity of hanging out in Angkringan carried out by teenagers into a routine activity every night. Based on observations that have been made over the past 2 months, that indeed many teenagers who do social relations hang out at night in angkringan places that are always filled with teenagers. Teenagers every day come to angkringan places just to buy a cup of coffee while smoking and going on for a long time. In this study, the method when collecting data used in-depth interviews of teenagers who hung out in angkringan and also used observation. The result is the phenomenon of hanging out in angkringan in adolescent relationships as a means of generating ideas and a place of outpouring. As an activity that raises ideas, namely by hanging out in angkringan, ideas, inspiration and creativity in the mind of informants can appear, with ideas that arise informants can install wireless LAN. As a place to outpour hearts by hanging out in angkringan, informants can meet with other friends, and have the opportunity to tell the problems they face, the outpouring of hearts that are usually discussed by informants is about love, work environment and so on